The third sector un Peru: dimensions and social potential - Sanborn, Cynthia A. (2000)
This article offers a brief overview of the role of the nonprofit sector in the Peruvian economy and society. lt also analyzes the principal advantages and limitations of private, nonprofit organizations as agents of development, with emphasis on the comparison of the contribution of nonprofits to that of the public sector and of private, for-profit enterprise.   First of all, the article describes the dimensions of the nonprofit or "third sector" in Peru, responding to the following questions: What weight do nonprofit organizations have in the national economy, in terms of employment and operating expenses? What are their main sources of funding? What share of the population participates in this third sector as volunteers, and/or as private donors? And finally, how does the Peruvian third sector compare to that of other countries? The article then analyzes the advantages and limitations of third sector organizations in the elaboration and implementation of social policy in Peru, comparing them to the other two sectors. lt ends with some conclusions and policy recommendations to take better advantage of the strengths of nonprofit organizations and overcome their limitations.